Brand Personalities of Global Wine Exporters: A Collective Reputation Theory Perspective. Issue 1 (2nd January 2018) - Rojas-Méndez, José I.; Hine, Michael J.; Rod, Michel
ABSTRACT: This study examines the perceptions of the personalities that wine drinkers attribute to the wines of the six top exporting countries. An exploratory study with an inductive approach was used, and data were collected from 757 wine consumers from 22 countries. Based on the collective reputation theory, we question the use of standardized versus localized strategy when approaching international markets by the top producers of the world. By means of correspondence analysis, our results indicate that each wine producer country tends to have a different positioning among consumers from different regions of the world. Besides, it is evident that a standardized approach to marketing and promotion of a specific country's wines to global markets could be viewed as rather myopic, representing a gross oversimplification of reality, and contradicting what our findings reveal about differences in global consumers' perceptions of wines from the big six producers.